Compartmental analysis of plasma and liver n-3 essential fatty acids in alcohol-dependent men during withdrawal - Pawlosky, Robert J. (American Society for Biochemistry and Molecular Biology, 2009)
The mechanism by which chronic ethanol consumption reduces concentrations of long chain polyunsaturated (LCP) fatty acids (FA) in tissues of humans was investigated in alcohol-dependent (AD) men during early withdrawal and to a well-matched control group by fitting the concentration-time curves of d(5)-labeled n-3 FA from plasma and liver, which originated from an oral dose of d(5)-linolenic acid (d(5)-18:3n-3) ethyl ester to a compartmental model. Blood sampled over 168 h and a liver specimen obtained 96 h after isotope administration were analyzed for d(5)-18:3n-3, d(5)-20:5n-3, d(5)-22:5n-3, and d(5)-22:6n-3. Plasma 20:5n-3 and 22:5n-3 were lower in AD subjects, compared with controls (20:5n-3: -50%, 22:5n-3: -34%). Increased amounts of d(5)-18:3n-3 were directed toward synthesis of d(5)-20:5n-3 in AD subjects (P < .05). However, this effect was offset by larger amounts of 20:5n-3 lost from plasma (control: 2.0 vs. AD: 4.2 mg d(−1)). In livers of AD subjects, more d(5)-18:3n-3 and d(5)-22:5n-3 were utilized for synthesis of d(5)-20:5n-3 (+200%) and d(5)-22:6n-3 (+210%), respectively, than was predicted from plasma kinetics. Although, the potential to utilize linolenic acid for synthesis of LCP FA was greater in AD subjects compared with controls, heightened disappearance rates of 20:5n-3 reduced overall plasma concentrations of several endogenous n-3 LCP FA.